Academic burnout in nursing students: An explanatory sequential design - Ali Asghar Ghods; Abbas Ebadi; Hamid Sharif Nia; Kelly‐Ann Allen; Tayyebeh Ali‐Abadi (Wiley, 2023)
Abstract Aim Despite the harmful effects of burnout among many nursing students, academic burnout is poorly understood. This study was conducted to better explain the concept of burnout in nursing students. Design An explanatory sequential mixed‐method design was used. Methods In the quantitative phase, the Maslach Burnout Inventory‐Student Survey was completed by 91 nursing students in eastern Iran. In the qualitative phase, individual interviews were conducted with 13 undergraduate nursing students, one nurse and one instructor. Data were analysed using the directed content analysis method. Results Results from an ANOVA test showed differences in burnout scores in different semesters (p = .02) that were confirmed by the qualitative data. In addition to the three dimensions of the Maslach burnout model (exhaustion, cynicism and inadequacy feeling), qualitative data from the present study indicated the presence of a fourth dimension (incompatible learning style).